2018
DOI: 10.1371/journal.pone.0199579
|View full text |Cite|
|
Sign up to set email alerts
|

The association between temperature, rainfall and humidity with common climate-sensitive infectious diseases in Bangladesh

Abstract: Bangladesh is one of the world’s most vulnerable countries for climate change. This observational study examined the association of temperature, humidity and rainfall with six common climate-sensitive infectious diseases in adults (malaria, diarrheal disease, enteric fever, encephalitis, pneumonia and bacterial meningitis) in northeastern Bangladesh. Subjects admitted to the adult medicine ward of a tertiary referral hospital in Sylhet, Bangladesh from 2008 to 2012 with a diagnosis of one of the six chosen cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
79
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 57 publications
8
79
3
2
Order By: Relevance
“…The decline of diarrhoea incidence rate was observed toward the end on drier season earlier to maximum rainfall. Similar findings have been reported by other researchers showing negative association between rainfall and diarrhoeal diseases [14,28]. Another study from Ghana reported a negative relationship between diarrhoeal diseases and rainfall by analyzing routine data reported on childhood diarrhoea [29].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The decline of diarrhoea incidence rate was observed toward the end on drier season earlier to maximum rainfall. Similar findings have been reported by other researchers showing negative association between rainfall and diarrhoeal diseases [14,28]. Another study from Ghana reported a negative relationship between diarrhoeal diseases and rainfall by analyzing routine data reported on childhood diarrhoea [29].…”
Section: Discussionsupporting
confidence: 88%
“…In addition to that a positively association was observed between increase of maximum temperature and increase of diarrhea cases. Similar findings have been elucidated in different studies [14,16,17,20,[23][24][25]. The increase cases observed during months with highest temperature justified by plausible explanations; higher temperature promotes the development of and growth of bacteria even though some evidences suggest that the survival and transmission of enteric viruses are increased during low temperature [26].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition to that a positively association was observed between increase of monthly average temperature and increase of diarrhea cases. Similar ndings have been elucidated in different studies [14,16,17,20,[23][24][25]. The increase cases observed during months with highest temperature justi ed by plausible explanations; higher temperature promotes the development of and growth of bacteria even though some evidences suggest that the survival and transmission of enteric viruses are increased during low temperature [26].…”
Section: Discussionsupporting
confidence: 84%
“…These components indirectly affect the condition of the human immune system. This condition is caused by climate changes that can increase the biting rate and vector reproduction rate and also shorten the pathogen incubation period (Chowdhury et al, 2018). This season's depiction of AFP cases can be used as information for monitoring and early detection so that it can increase the vigilance of medical personnel to carry out prevention in the case-increasing month.…”
Section: Overview Of Afp Cases Based On Time Variablementioning
confidence: 99%